Pengaruh Atribut-Atribut Kualitas Audit Terhadap Kepuasan Klien - ., Fadhlurokhman; ., Nurdhiana (Jurnal Ilmu Ekonomi ASET, 2009)
The purpose of the research is to find out the influence of experience in auditing,comprehend clientsâ industry, responsive to clientâs need, obey to general standard, and KAPleadersâ involvement toward clientsâ satisfaction at manufacture companies in Semarang.Whereas, the sample of this research is 31 financial managers or controllers at big manufacturecompany in Semarang. The statistical analysis in this research is multiple linear regression.There are four results of partial hypothesis test. First, it shows that experience in auditing haspositive significant influence toward clientsâ satisfaction. Second, the hypothesis test ofcomprehend clientsâ industry indicates positive significant influence toward clientsâ satisfaction.Third, the test hypothesis of responsive to clientsâ need has significant influence toward clientsâsatisfaction. Then, the test of obeying to general standard shows positive significant influencetoward clientsâ satisfaction. The test of KAP leadersâ involvement also shows positive significantinfluence toward clientsâ satisfaction. The result of simultaneous hypothesis test indicates thatthere is significant influence of experience in auditing, comprehend clientsâ industry, responsiveto clientâs need, obey to general standard, and KAP leadersâ involvement toward clientsâsatisfaction.Keywords : experience, comprehension, response, obidience, involvement, satisfaction.